Estimation of greenhouse gas emissions from spontaneous combustion/fire of coal in opencast mines – Indian context - Mohalik, N.K.; Lester, Edward; Lowndes, Ian; Singh, V.K. (Taylor & Francis, 2016)
There are a significant number of uncontrolled coal mine fires (primarily due to spontaneous combustion of coal), which are currently burning all over the world. These spontaneous combustion sources emit greenhouse gases (GHGs). A critical review reveals that there are no standard measurement methods to estimate GHG emissions from mine fire/spontaneous combustion areas. The objective of this research paper was to estimate GHGs emissions from spontaneous combustion of coals in the Indian context. A sampling chamber (SC) method was successfully used to assess emissions at two locations of the Enna Opencast Project (OCP), Jharia Coalfield (JCF), for 3 months. The study reveals that measured cumulative average emission rate for CO2 varies from 75.02 to 286.03 gs−1m−1 and CH4 varies from 41.49 to 40.34 gs−1m−1 for low- and medium-temperature zones. The total GHG emissions predicted from this single fire affecting mines of JCF vary from 16.86 to 20.19 Mtyr−1